Algebra Reasoning Ability Viewed From Student Gender Differences - Kurniyasih, Nur; Nugraheni, Esti Ambar (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Algebraic reasoning skills are important for students to master, with algebraic reasoning students are able to solve everyday problems in algebraic form. Gender is one of the factors that differentiates students' reasoning abilities in solving math problems. This study aims to describe algebraic reasoning in terms of gender differences. This type of research is qualitative with research subjects of four students taken from 31 students, Middle School class VIII by selecting two female students and two male students based on the average score level of each gender in solving System of linear equations of two variables questions based on indicator of algebraic reasoning ability. Data collection techniques in this study were tests, interviews and documentation. The results of this study indicate that the algebraic reasoning of female subjects is higher than that of male subjects. Some of the factors for the low algebraic reasoning of the subject include: the subject is not careful and forgets the formulas that have been taught.